Allogeneic hematopoietic stem cell transplantation in T-cell lymphoma: a Meta-Analysis. Issue 4 (21st March 2022) - Singh, Vijendra; Kim, Seongho; Deol, Abhinav; Uberti, Joseph P.; Modi, Dipenkumar
Abstract: T-cell lymphoma (TCL) poses a therapeutic challenge. Allogeneic stem cell transplant (alloSCT) is frequently offered in primary refractory disease or failed autologous transplant. We systematically searched published articles on outcomes of alloSCT in TCL through PubMed and EMBASE database between January 2000 and October 2019. Among 651 identified studies, 22 (888 patients) were included. Forty percent patients had peripheral T-cell lymphoma not otherwise specified, 15% had angioimmunoblastic T-cell lymphoma, 21% had anaplastic large cell lymphoma, 5% had cutaneous T-cell lymphoma, and 19% had other histologic subtypes. Thirty-six percent patients had relapsed/refractory disease. Myeloablative conditioning regimens were used in 55% patients. At two-, three- and five-year post-transplant, overall survival was 57, 54 and 51%, respectively; progression-free survival was 45, 50 and 45%, respectively; non-relapse mortality was 9, 29 and 29%, respectively; relapse rate was 30, 28 and 29%, respectively. Our study shows that alloSCT provides durable remission in T cell lymphoma.